2007
DOI: 10.1124/dmd.107.017012
|View full text |Cite
|
Sign up to set email alerts
|

Identification of New Flavone-8-Acetic Acid Metabolites Using Mouse Microsomes and Comparison with Human Microsomes

Abstract: ABSTRACT:Flavone-8-acetic acid (FAA) is a potent anticancer agent in mouse but has not shown activity in humans. Because FAA metabolism could play a role in this interspecies difference, our aim was to identify the metabolites formed in vitro using mouse microsomes compared with those in human microsomes. Mouse microsomes produced six metabolites as detected by reversed-phase highperformance liquid chromatography-mass spectrometry (MS). Three metabolites were identified as the 3-, 4-, or 6-hydroxy-FAA, by comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Flavone‐8‐acetic acid (FAA) and its monohydroxylated derivatives at positions 3, 5, 7, 2′, 3′ or 4′ were kindly provided by Dr Jean‐Jacques Berthelon (Merck‐Lipha Santé, Lyon, France). The 6‐OH‐FAA was synthesized according to our previously described methodology using appropriate starting materials 13–16. Standard solutions at 5 µg/mL of each derivative were prepared in methanol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavone‐8‐acetic acid (FAA) and its monohydroxylated derivatives at positions 3, 5, 7, 2′, 3′ or 4′ were kindly provided by Dr Jean‐Jacques Berthelon (Merck‐Lipha Santé, Lyon, France). The 6‐OH‐FAA was synthesized according to our previously described methodology using appropriate starting materials 13–16. Standard solutions at 5 µg/mL of each derivative were prepared in methanol.…”
Section: Methodsmentioning
confidence: 99%
“…As part of an ongoing project on FAA metabolism, we have previously shown that FAA can be metabolized in vitro into several monohydroxylated metabolites using mouse microsomes 13. The challenge of FAA metabolite identification led us to consider every possible position where a hydroxyl group could be found on the parent compound after phase 1 metabolism by cytochrome P450s, for example.…”
mentioning
confidence: 99%
“…Other phenylated drugs can be metabolized to an epoxy derivative, which is then opened by epoxide hydrolase to form a catechol ring, which then is oxidized to an oquinone. In the case of flavone-8-acetic acid, the resultant catechol derivative [Pham et al, 2007] can be expected to form an o-quinone in which the double bonds are conjugated with the adjacent flavone pyrone group. This additional allylic ketone group should enhance the activity.…”
Section: Bioactivation Of ''Almost Allylic'' Drugsmentioning
confidence: 99%
“…Out of 78 articles included in the analysis (42 in vitro, 42 in vivo, and 16 clinical studies), 47 (60.3%), 14 (17.9%) and 17 (21.8%) articles respectively, investigated metabolite profiles of conventional anticancer drugs/synthetic anticancer candidates, small-molecules targeted therapy, and herbderived compounds with anticancer activities. These studies involved a total of 57 (57.0%) conventional anticancer drugs/ synthetic anticancer candidates, 6, 22 (22.0%) studies for small-molecules targeted therapy, 4,5,[59][60][61][62][63][64][65][66][67][68][69][70] and 21 (21.0%) studies for herb-derived compounds with anticancer activities 2,3,7,9,[71][72][73][74][75][76][77][78][79][80][81][82][83] (Tables 1-3). Anticancer drugs or candidate compounds are metabolized by either Phase I, or phase II metabolizing enzyme alone, or both phase I and phase II metabolizing enzymes.…”
Section: Study Descriptionmentioning
confidence: 99%